THE WORKDAY THAT HELPED TO SAVE THE SOVIET KOLKHOZES I HAVE MANY COUPLETS TO SING, AND EVEN MORE WORKDAYS (FROM THE REPERTOIRE OF M. MORDASOVA, A SOLOIST OF THE VORONEZH PEOPLE’S CHOIR, THE USSR PEOPLE’S ARTIST) - Shubin, Sergey (Revista Inclusiones, 2020)
In this year, it is exactly 50 years after the kolkhoz (collective farm) workday was abolished in the Soviet Union. The author doubts the N.S. Khruschev’s thesis that “...the kolkhoz workday cannot be acknowledged a right and objective measure of labor costs for production” in modern market environment that leads to the degradation of Russian villages. The article justifies more objective evaluation of the workday as a measure of quantity and quality of the kolkhoz members’ labor and a way to stimulate it, especially since the Soviet kolkhozes outlived the abolition of the workday (which played an important role in the agricultural policy of the country from 1930 to 1966) for a little while.